DAVID HERBERT LAWRENCE AN ICON OF MODERNISM - Ejupi, Vlera; Siljanovska, Liljana; Iseni, Arburim (European Scientific Journal, ESJ, 2014)
A great contribution on the exploration of the human mind, and themodes in which people think and behave by literally leaving aside all theconstraints that were imposed to them by various social movements, arepresent in the Literature of the modern world, which historically begins bythe ending of the 19th century. The era during which this kind of Literatureis created is known as Modernism. Modernism is based on the outburst ofpeoples introversion, their pathological need to speak freely about their―skeletons in the cupboard‖, to get released of their mental and spiritualxenophobia. Modernism enabled not only a detection of these deformities,but freedom to speak about them and find cures. It is Sigmund Freud, whosetheories changed the way of thinking, thus the way of writing that is whyModernism transfers us to a new dimension of writing, which deals a lot withthe straightforward way of writing about the truth in a truthful way. There isno doubt that David Herbert Lawrence is the icon of the Period ofModernism in British as well as the world Literature. It is Lawrence whogave directions how to cope with the difficulties of modern era. Not onlydoes he encompass the above mentioned elements, but he goes even fartherwithin the exploration of our Eros and Thanatos, then also with the ideals ofthe society in the new spheres where they happen to find themselves. Hemanaged to put so much of his life in his books, and managed to createcharacters which are considered as the most completed ones in the history ofLiterature. So the following text is nothing but a modest try to penetrate intothe inner feelings of the protagonists in his novel ―Women in Love‖. It is the 112relations among the protagonists that make the readers feel free.